“Forging the Fatherland”: Work and vocational education in Argentina during Peronism (1944–1955). - Oelsner, Verónica (Paedagogica Historica, 2013)
This article focuses on the reforms in the field of vocational education, as well as on representations related to work, in Argentina during Perón’s political leadership. In the framework of far-reaching economic reforms and social transformations, while in the position of secretary of labour (1943–1945) Perón started a vocational education system, which grew notably during his presidency (1946–1952 and 1952–1955). At the same time, his government not only defined the worker as the protagonist of its policy but deliberately constructed and broadly disseminated positive representations of manual work, the worker, the apprentice and his training that were aimed at replacing older ones. After Perón’s overthrow in 1955, the succeeding governments brought the political centrality of the worker to an end and repressed all symbology related to him. In the following years, the vocational education system created during the Peronist era gradually fell apart. This article analyses the relationship between these phenomena. It assumes that vocational education is not just shaped by economic demands or technological development. It rather believes that, as the analysis of the Peronist case shows, social representations related to work and education can also play an important role, supporting, hindering or impeding the establishment or development of specific vocational education models.